The importance of clarity: Impacts of Colombia's Lenguaje Claro Program on reducing administrative burdens - Ana Cuesta; Angela Reyes; Benjamin Roseth (Inter-American Development Bank (IDB), 2019)
Citizens confront multiple challenges when attempting to access public services. This article focuses on an aspect yet unaddressed by existing literature on administrative burdens: the complexity of the written language used by government agencies in Latin America. It presents an impact evaluation of the Lenguaje Claro Program of Colombia's National Planning Department. A randomized control trial compared two versions of a letter - the original and one with plain language - used by the property department of the city of Bogota. The study shows that clarifying content via modifications in language, content order, and formatting can reduce citizen's learning costs. Plain language thus has positive effects for both individuals and public institutions. A complementary perception survey revealed that there is significant room for additional simplification, as both the original and the plain language letter were largely poorly rated by citizens.
Keywords: C93; H11; H83; Z13; Z18; 330; administrative burden; language simplification; plain language; public services; red tape